2017
DOI: 10.1111/jam.13549
|View full text |Cite
|
Sign up to set email alerts
|

Response of microbial community and catabolic genes to simulated petroleum hydrocarbon spills in soils/sediments from different geographic locations

Abstract: When developing practical in-situ bioremediation approaches for PHs contamination of soils/sediment, appropriate microbial community structures and the abundance of PH-degrading genes appear to be influenced by geographic location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The results presented above are consistent with the results of research on the metagenomes of oil-contaminated soils. Some authors found an increase in the share of Proteobacteria in soil samples, particularly Gammaproteobacteria 14 16 , 84 , 85 , which indicates that this is the best-adapted phylogenetic group for hydrocarbon pollution, particularly in cold environments. They also noted an increase in the abundance of Bacteroidetes, Firmicutes, and Actinobacteria; apparently, in acidic soils of cold climatic zones, an increase in the abundance of Actinobacteria was more noticeable whereas in areas with a warm climate and more alkaline soils, the shares of Bacteroidetes and Firmicutes, which were numerous, also increased.…”
Section: Resultsmentioning
confidence: 99%
“…The results presented above are consistent with the results of research on the metagenomes of oil-contaminated soils. Some authors found an increase in the share of Proteobacteria in soil samples, particularly Gammaproteobacteria 14 16 , 84 , 85 , which indicates that this is the best-adapted phylogenetic group for hydrocarbon pollution, particularly in cold environments. They also noted an increase in the abundance of Bacteroidetes, Firmicutes, and Actinobacteria; apparently, in acidic soils of cold climatic zones, an increase in the abundance of Actinobacteria was more noticeable whereas in areas with a warm climate and more alkaline soils, the shares of Bacteroidetes and Firmicutes, which were numerous, also increased.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, total microbial respiration in our microcosms increased following the application of naphthalene on days 17 and 38 (Fig 1). The reduced response in the first 10 days of application may be due to the restructuring of microbial populations under short-term environmental stresses [39, 40]. This finding corresponds to an obvious fluctuation in the ratios of fungi to bacteria, G + to G - bacteria and MBC to MBN in the naphthalene microcosm (Fig 2E and 2F, Fig 3C), which is in agreement with the results showing a reduction in the radial growth of fungal cultures after 6 days of naphthalene treatment [16].…”
Section: Discussionmentioning
confidence: 99%
“…DNA extracts from contaminated soil (DO microcosms) at days 14 and 63 were used for cloning of the alkB gene. PCR reaction components were as for 16S rRNA gene amplifications, except that the alkB forward (5'-AACTACMTCGARCAYTACGG-3') and reverse (5'-TGAMGATGTGGTYRCTGTTCC-3') primers (Liu et al, 2017) were at a final concentration of 0.4 mM in a total reaction volume of 50 l. PCR amplification was carried out at 94 °C for 3 min, followed by 30 cycles of 94 °C for 45 s, 50 °C for 60 s, 72 °C for 90 s, with a final extension at 72 °C for 10 min. Correct alkB amplicons of ~100 bp were purified from 1.5% (w/v) TAE-agarose gels, cloned into pCR2.1 using a TA cloning Kit (Invitrogen) according to the manufacturer's instructions and submitted for Sanger sequencing (University of Dundee, UK).…”
Section: Qpcr Of the Alkb Genementioning
confidence: 99%
“…In soils, while it has been suggested that community responses are more diverse and less pronounced, highly specific blooms of genera such as Alkanidiges have also been reported (Fuentes et al, 2016). The abundances of primary hydrocarbon-degrading genes such as alkane 1-monooxygenase (alkB), naphthalene dioxygenase (nah) and phenol monooxygenase (phe) also increase as a result of these community changes (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%